Hubungan Intensitas Penggunaan Sosial Media dengan Prokrastinasi Akademik Siswa MTsN 2 Bukittinggi - Suryani Suryani; Afrinaldi Afrinaldi; Hidayani Syam; Muhiddinur Kamal (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
This paper examines the relationship between the intensity of social media use and academic procrastination in students of MTsN 2 Bukittinggi. Using a correlative quantitative method, this study found that students' intensity of social media use has a significant relationship with their academic procrastination. The hypothesis was accepted with a considerable correlation value (0.431), and the positive correlation indicated that the higher the intensity of social media use, the higher the level of students' academic procrastination. Achieving these results through proper fieldwork and data processing demonstrates the relevance and validity of this study. Therefore, the conclusion of this study is that there is a significant correlation between the intensity of social media use and academic procrastination among MTsN 2 Bukittinggi students.